Análisis comparativo de la Parrilla de Programación entre el Canal 6 de la Ciudad de Babahoyo y RTV 3 Canal de Vinces - Villacres Sandoya, Joselyn Lissette (2020)
The present work writes the comparative analysis between the television entities from Fluminense in the province of Los Ríos such as RTV 3 in the canton of Vinces and Channel 6 of Babahoyo which are a means of private self-management and the impact and echo on the different social and cultural groups in each of these cantons through their daily television programming schedule. Based on the compilation of bibliographic data to establish a comparison of characteristics, similarities and strengths and weaknesses of these television communication organizations in their productions and audiovisual broadcasts throughout the week in the projection of cultural, educational, informational and entertainment programs for their general public and how these programs provide their contribution to society. Therefore, a bibliographic analysis of the different programming that these channels offer to their audience at different times was established in order to know the impact and echo that they have on the different social and cultural groups of these Fluminense cantons to establish indicators that help to understand how the television schedule is generated to establish how the existing link between television producers and viewers is generated.